Purification of dye industries wastewater via crystallization: effect of operation time and solution concentration / Mohd Nizamuddin Mohd Zolfakar - Mohd Zolfakar, Mohd Nizamuddin (2018)
The high capacity of water consumption also results in high amount of wastewater produced and released to ecosystem and will affect the ecology. Purification of dye wastewater using crystallization, specifically freeze concentration technique provides more width to any process plants towards waste management. It is essential to introduce a new method of freeze concentration to overcome the weaknesses of conventional method, and therefore to enhance the wastewater purification development for a better quality of water treatment. Study of the effect of operation time towards effective partition coefficient, K and solute recovery, Y of methylene blue dye wastewater was performed using operation time from t = 5 minutes to 25 minutes. The result showed that effective partition coefficient increases with increasing time, also resulted in decreasing solute recovery of the solution. The effect of solution concentration towards K and Y values was also studied using initial solution concentration, C0 = 300 mg/L to 700 mg/L and the results showed differently from other studies.